Liquidity Constraints and the Cyclical Behavior of Markups - Scharfstein, David; Chevalier, Judith A. (American Economic Review, 1995)
During business-cycle expansions, wages appear to rise relative to output prices.1 This fact is easy to square with real-business-cycle models which are based on the assumption that labor is more productive during expansions. But it is inconsistent with standard business-cycle theories based on aggregate demand fluctuations. In these models, fixed technology and diminishing returns imply that labor becomes less productive as output rises. Thus, in an expansion, wages should fall relative to output prices. Julio Rotemberg and Michael Woodford (1991, 1992) argue that imperfect competition can help to reconcile aggregatedemand theories of business cycles with observed procyclical real wages. If firms compete more aggressively during expansions, reducing the markup of price over marginal cost, the real wage can be driven up even if labor's marginal product falls. Countercyclical markups can therefore induce procyclical real wages. The difficult issue is understanding why markups would be countercyclical. Rotemberg and Garth Saloner (1986) and Rotemberg and Woodford (1991, 1992)hereafter referred to as RSW-claim that markups are countercyclical because it is harder for oligopolistic firms to sustain collusive prices during booms. When current demand is high relative to future demand, the incentive for any firm to cut its price rises because it becomes more valuable to capture current sales than to maintain collusion in the future. RSW present evidence that markups are indeed more countercyclical in more concentrated industries (where collusion can be more easily sustained). While this finding is consistent with countercyclical collusion, it is also consistent with any other theory in which imperfect competition induces firms to compete more aggressively during booms. In this paper, we analyze an alternative theory of countercyclical markups based on imperfect competition and capital-market imperfections. This theory has been suggested by Bruce Greenwald et al. (1984), Nils Gottfries (1991), and Paul Klemperer (1993). We present some preliminary evidence in an effort to distinguish this explanation from countercyclical collusion.